Assessing environmental sustainability of HPLC methods for tri-combination anti-hypertensive drug analysis - Naga Prashant K; Pragathi Y; Suvarna Yenduri (Green Analytical Chemistry)
Ecological issues are raised by analytical research methods that harm the environment, such as liberating dangerous solvents into the atmosphere. Sustainable analytical techniques should consider method performance, eco-friendliness, productivity, and practicality to reduce these difficulties. These consequences can be reduced by evaluating sustainability using measures called green metrics, blue metrics and sustainability metrics. The purpose of this study was to evaluate the environmental sustainability of the current HPLC techniques for tri-combination anti-hypertensive medication analysis. This study collects and evaluates the greenness, whiteness, and blueness of amlodipine besylate, indapamide, and perindopril drugs using the HPLC method. A range of metrics are used, including National Environmental Methods Index (NEMI), Analytical Eco-scale, Analytical GREEnness prep (AGREE prep), Modified-Green Analytical Procedure Index (MoGAPI), RGB fast, Analytical Method GREEnness Score (AMGS), Analytical Method Volume Intensity (AMVI), Blue Applicability Grade Index (BAGI), and HEXAGON. For some measurements and scores in other situations, the percentages of greenness, whiteness, and blueness for the chosen approaches were displayed as pictograms utilizing the evaluation tools. To determine the optimal option from the existing methods, the sustainability outcomes of the chosen approaches have been measured and compared. As an alternative to conventional methods, Methods 2 and 3 have the potential to be sustainable and ecologically beneficial. Safety and responsible consumption were superior to those of the other chromatographic methods.The study provided a clear understanding of the methodology's advantages and disadvantages in terms of green, white, and blue features, making it simple for the analyst performing the analysis to choose the most appropriate analytical approach.